A dynamic approach to measure the impact of freight transport on air quality in cities. (10th December 2019) - Mommens, Koen; Brusselaers, Nicolas; van Lier, Tom; Macharis, Cathy
Abstract: Air pollution is recently considered as largest treat to human health. Freight transport vehicles are responsible for a large share of the air pollution. The impact of pollutants is heavily depending on the number of people present in the proximity of the emission source. This impact is generally calculated using the impact-pathway-approach. Yet, the geo-temporal link between the emission source and the number of people in proximity of that source is currently considered to be static. This research presents the combination of dynamic receptor densities and dynamic emission sources by quantifying the impact of air pollution (particulate matter and mono-nitrogen oxides) generated by freight transport in the Brussels Metropolitan Region. The results of this new approach were compared to the current practice in literature. Very large differences, up to factor 45, were found on the local level. The proposed dynamic methodology should consequently be used for micro-scale analyses on transport related air pollution. However, the overall difference for the entire Brussels Metropolitan Region is neglectable (0, 5%). Highlights: External cost calculation of NOX and PM pollution generated by freight vehicles in the Brussels Metropolitan Region. Comparison between static impact-pathway approach and dynamic approach using dynamic receptor densities. Large differences in external costs are found on the local level. Neglectable differences in external costs are found for the entire region.